Research Progress in Single-Cell Omics Technology in Intestinal Health - XU Tongxiao, CHEN Yanan, WANG Jiantang, HUANGFU Bingxin, BAN Qiushi, HUANG Kunlun, HE Xiaoyun (Shipin Kexue, 2025)
The intestine serves as an important digestive and immune organ in the animal body, which is responsible for the digestion and absorption of nutrients in foods. The body can affect all physiological processes except digestion by activating the gut-organ axis. A healthy diet provides the body with the nutrients it needs, helping to maintain intestinal microbial balance and thereby promoting intestinal health; conversely, an unhealthy diet may lead to intestinal problems, and intestinal health directly correlates with overall bodily health. Traditional omics techniques are performed on a multicellular basis and often overlook information on cellular heterogeneity. Single-cell omics technology allows for simultaneously detecting and comparing the expression of single-cell genomes, which provides a new perspective on the study of intestinal microbial community and intestinal health. This article reviews the application of single-cell omics in intestinal health, which is expected to provide new insights into understanding the physiological function and mechanism of the gut, and provide a scientific basis for improving human health.